The changing interaction of ethnic and socio-economic segregation in England and Wales, 1991–2011. (June 2017) - Harris, Richard; Johnston, Ron; Manley, David
Following the publication of the 2001 and 2011 Census data, considerable attention has been given to patterns of ethnic residential segregation within the UK. The evidence contributes to debates about integration; however, asKapoor (2013) has argued, discussion about it also risks promoting the idea that what we measure is voluntary segregation, arising from the outcome of residential choices and a preference to live with one's ethno-cultural peers. In reality, ethnic and social segregation overlap and are easily confounded; it is important to pay attention to where they geographically coincide. In this paper we use an area typology to assess whether minority ethnic groups are disproportionately concentrated in neighbourhoods in England and Wales containing the lowest proportions of their adult populations in full-time employment, and evaluate how those concentrations have changed between 1991 and 2011. We consider the (residential) exposure of the ethnic groups to the White British and also to each other, and identify the groups affected by the persistence of economic disadvantage. The analysis shows that patterns of ethnic segregation intersect strongly with neighbourhoods of socio-economic disadvantage, with inequalities in the labour market and the increase of part-time working suggested as contributing factors. A decreased exposure to the White British is an increased characteristic of the disadvantaged neighbourhoods where minority groups live. However, exposure between those groups has increased.